Judicial Decision-Making and the Realization of Justice in the Indonesian Criminal Law - Haryadi, Slamet; Ja’far, A. Kumedi; Dwiono, Sugeng; Fikma Edrisy, Ibrahim; Dwi Subarkah, Amirah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The phrase "For the Sake of Justice Based on Belief in the One Almighty God" serves as the foundational principle for the administration of justice in Indonesia and appears as the irah-irah (heading) in court decisions issued by the Supreme Court of the Republic of Indonesia. This study examines how this principle is reflected or not reflected in first-instance corruption case rulings. Through a normative legal research approach, this study employs the theory of justice as its analytical framework. Focusing on decisions from the Tanjungkarang and Banda Aceh District Courts, it finds that judicial reasoning in these cases often lacks legal arguments that embody the values of justice rooted in belief in the One Almighty God. The study argues that a judicial decision with integrity must go beyond a mere recital of the facts and legal elements of the indictment. It should also offer moral reasoning that acknowledges the accused as a human being with dignity and inherent rights to justice, truth, and fair treatment. The analysis also highlights instances where judges, in applying Indonesia’s anti-corruption laws, appear to act not in accordance with religious moral values, but rather under the influence of external interests. Such actions, including legal simplification, selective application, and even corrupt practices such as bribery, compromise the moral foundation of judicial decisions and result in unjust outcomes. Theoretically, this research affirms that to realize justice in its truest form, judges must draw upon divine moral principles as a source of inspiration and guidance. Only then can court decisions reflect both human dignity and substantive justice.